Prevalence and associated risk factors of musculoskeletal disorders among information technology (IT) professionals: A systematic review - Prasetya, Tofan AE.; Mamun, Abdullah A.; Rahmania, Aisy; Ahmed, Mobashwer; Uddin, Abu SMS.; Nilamsari, Neffrety; Wardani, Ratnaningtyas WK. (Narra J, 2024)
Musculoskeletal disorders (MSDs) are a growing concern among information technology (IT) professionals. Understanding the specific risk factors associated with MSDs among employers, occupational health practitioners, and IT professionals may reveal effective preventive measures. The aim of this study was to examine the prevalence and identify the risk factors associated with MSDs among IT professionals. A comprehensive literature search was conducted on several databases, including PubMed, Scopus, ScienceDirect, ProQuest, Online Library Wiley, Springer, Web of Science, and manual searches to identify relevant studies published between 2013 and 2023. The search strategy employed appropriate keywords related to IT professionals, musculoskeletal disorders, prevalence, and risk factors. Two reviewers independently assessed each article using PRISMA guidelines and the Joanna Briggs Institute’s (JBI) Critical Appraisal Checklist for Prevalence Data. Data extraction was performed, and a narrative synthesis was conducted to summarize the findings. Our search yielded a total of 1159 records, with 13 studies finally included in this review. The selected studies were from several countries and contained a total of 4632 participants. The prevalence of MSDs was reported with a maximum rate of 89% and a minimum rate of 20%, reflecting the overall percentage of affected individuals and including data on specific body areas affected. Identified risk factors from the selected studies include work duration, experience, sex, strenuous back positions, smoking, physical inactivity, MSD history, uncomfortable workstation setting, mental stress, insufficient sleep, body posture, exercise status, alcohol consumption, prolonged sitting, workspace, job demands, overexertion, breaks during work, and excessive usage of smartphones.